Consumer Behavior in Omnichannel Retail - Uswatun Khasanah, Aulia; Karin Rizkiawan, Ilham; Hadi Utomo, Fahman; Yuniarti, Uli; Sari Dewi, Multi (International Journal of Management Science and Information Technology, 2023)
Retail industry has undergone significant changes in the digital era, with companies offering multiple channels for shoppers to purchase goods. As a result, consumers now have more options to make shopping decisions. This study aims to examine how consumers behave when buying goods from a retail store that has multiple channels. The research method used was qualitative, and the sample size consisted of 11 fashion product consumers. The results showed that most of the respondents preferred to use online platforms to purchase fashion products. They used these platforms to check for discounts, promotions, and product information. However, they still made purchases offline when attractive offers were available, or to ensure that the product matched their expectations.